Adherence to 24-hour movement guidelines and academic performance in adolescents. (June 2020) - Lien, A.; Sampasa-Kanyinga, H.; Colman, I.; Hamilton, H.A.; Chaput, J.-P.
Abstract: Objective: The aim of the study was to examine the association between meeting combinations of the Canadian 24-h movement guidelines and academic performance in adolescents. Study design: This cross-sectional study used the 2017 Ontario Student Drug Use and Health Survey, a survey representative of Ontario students in grades 7–12 attending publicly funded schools. A total of 10, 160 students were included in the analysis. Methods: Moderate to vigorous physical activity (MVPA), screen time, sleep duration, and academic performance were self-reported. A multiple linear regression model was used to examine differences in academic performance between adolescents meeting and those not meeting the combinations of movement guidelines (≥60 min/day of MVPA; ≤2 h/day of screen time; 9–11 h/night of sleep for ages 11–13 years, 8–10 h/night for ages 14–17 years, and 7–9 h/night for ages 18 years or older). Covariates included age, sex, ethnicity, subjective socio-economic status, body mass index z-score, and substance use. Results: We found that 5.1% of students met all three movement guidelines, whereas 39.0% did not meet any. Middle school students who met all three guidelines or either the screen time or sleep guideline displayed better academic performance than those who met none of the guidelines. High school students who met the screen time and sleep guidelines displayed better academic performance than those who did not meet any guidelines. Conclusions: Adhering to screen time and sleep duration recommendations is associated with better academic performance among adolescents. Highlights: Of all students, 5.1% met all three movement guidelines, whereas 39.0% did not meet any. Sleep and screen time are more linked with academic achievement than physical activity. Some differences were found between middle and high school students.